Discours de l’exiguïté comme littératures-mondes ? - Silvia U. Baage (Carnets)
This article examines one of the discourses of smallness that François Paré refers to as « island literature ». I will analyze the concept of the island fragment to understand if any affinities exist among models of transculturality that describe writing without borders the way this term is understood by island authors, the advocates for world literature in French, and literary critics. I will look at two anthologies, the collection « Miniatures: Nouvelles du Monde » (published in Paris) and the collection of transoceanic short stories Partir sans passeport (Idem, 2011). My analysis will first focus on the epistemological function of the fragment and then move to the « double-minorisation » of space (the island) and genre (the short story). In the last section, I will show that in the short stories in question, writing the fragment takes into consideration the experience of exile and migration in its various forms. Is the writer of the margins condemned to express himself in a « minor » genre to make his voice heard?